Analisis Wacana Berita Hoaks tentang Program Makan Bergizi Gratis (MBG) Menggunakan Pendekatan Socio-Cognitive Teun A. van Dijk - Setyawan, Endy; Rianto; Kusuma Wardana; Sugihartanto; Rizal Angko Pratama; Malik Ibrahim (Jurnal Audiens, 2025)
This study aims to analyze the discourse of hoax news related to the Free Nutritious Meal Program (called as Makan Bergizi Gratis (MBG) circulating on social media using Teun A. van Dijk’s socio-cognitive approach. These government-attributed hoaxes contain various linguistic and discursive strategies designed to manipulate the cognitive schemas of the public, such as false legitimacy, promises of high salaries, negative framing, and urgent calls to action. Using qualitative research methods and discourse analysis, five main examples of hoaxes were examined, involving issues of program cancellation, fake volunteer recruitment, milk import claims, and allegations of deaths caused by the MBG program. The analysis reveals that these hoaxes not only spread false information but also effectively exploit the audience’s fears, economic needs, and group identities, thereby causing public unrest and decreasing trust in government programs. The findings underscore the importance of media literacy and appropriate communication strategies as efforts to mitigate hoaxes and strengthen public trust in social welfare programs